Entrepreneurial Behaviors: Are the People Restricted by Knowledge Inertia? - Cavus, Mustafa Fedai; Koc, Murat; Aksoy, Alptug (International Review of Management and Marketing, 2013)
The purpose of this study is to scrutiny the impact of knowledge inertia on entrepreneurial behaviors of university students. Two dimensions of knowledge inertia –learning inertia; to acquire knowledge insistently on the same source and experience inertia; to use the former methodology and past experience persistently while encountering the difficulties-and entrepreneurial behaviors are investigated through the questionnaire. In this regard, the relationship of the two dimensions of knowledge inertia with entrepreneurial behavior was investigated. After collecting and analyzing the data, the results indicate that there is a meaningful relation between knowledge inertia and entrepreneurial behavior. There is also meaningful negative relation between learning inertia and entrepreneurial behavior. On the other hand, there is a positive relationship between experience inertia and entrepreneurial behavior. Keywords: Knowledge inertia, learning inertia, experience inertia, entrepreneurial behavior. JEL Classifications: M00; M10